High Brightness Pulps as Filter for the Production of Urea formaldehyde & Melamine formaldehyde Moulding Powder - Guha, S. R. D.; Singh, Man Mohan; Singh, S. P. (Indian Forester, 1978)
High brightness pulps suitable for use as Filler for Urea formaldehyde and Melamine formaldehyde moulding powder have been prepared from unbleached and bleacbed bamboo sulphates pulps of Central Pulp Mill, Fort Sondgarh by suitable bleaching process and from Eucalyptus hybrid wood by prehydrolysis sulphate process followed by multi stage bleaching process. These pulps were evaluated by Nuchem Plastics Ltd., Faridabad and fouod suitable.